The role of fluorination during the physicochemical erosion of yttria in fluorine-based etching plasmas. Issue 2 (February 2022) - Kindelmann, Moritz; Weber, Moritz L.; Stamminger, Mark; Buschhaus, Rahel; Wessel, Egbert; Bram, Martin; Guillon, Olivier
Highlights: First description of an orientation dependent surface fluorination during plasma erosion of Y2 O3 . Direct correlation of the material properties of Y2 O3 ceramics with the erosion behavior. Surface fluorination is the major driving factor controlling the etching resistance and the surface morphology. A comparison of Y2 O3 and YOF at the microscopic scale underlines the strong impact of surface fluorination. Abstract: A physicochemical mechanism acting between the reactive plasma and the material surface controls the erosion of polycrystalline ceramics in fluorine containing etching plasmas. In this study, a Y2 O3 /YOF composite was exposed to a fluorine etching plasma. Relocalization enables the direct correlation of crystalline orientation with material response. Our study reveals an orientation dependent surface fluorination of Y2 O3, which controls the etching resistance and morphology formation. Orientations near the low index planes (001), (010) and (100) exhibit the lowest stability due to a homogeneous surface reaction. The presented results help to extend the mechanistic understanding of the plasma-material interaction of Y2 O3 .